Caracterización y propuesta técnica de la acuacultura en el sector comprendido entre las comunas ayangue y montañita de la península de Santa Elena. - Serrano, David (2009)
The area located between the towns of Ayangue and Montañita is one of the zones where development related to tourism has been most important during the last few year, this development has contributed with infrastructure and strengths that indirectly benefit aquaculture related activities, which mainly revolve around hatcheries and brood stocking. The main source of development and technological innovation, together with private enterprises like EXPALSA, has been CENAIM (National Center of Aquaculture and Marine Research); these two components lead research that has raised the productive competitiveness of the industry. As is the case in the rest of the country, due to its geographical location, the conditions present in the above mentioned area translate in high potential for the aquaculture industry in general, which is why the reproduction and grow out of L. vannamei has continued successfully, in spite of the White Spot event. This continued success is attributed to 5 of the 18 centers for these purposes registered by the competent authorities in 2007. The best options for aquaculture development in the area are working in alliance with CENAIM as well as with producers looking to increase their competitiveness and take advantage of tourism